Pandangan Hidup dan Simbol-Simbol Dalam Budaya Jawa - M. Muslich (Millah: Journal of Religious Studies, 2004)
Javanese Society is unity bounded by the norm of  life, that of  tradition and religion. The fundamental characteristic of  it is having dynamic, tolerant, acomodative and optimistic religiousity spirit. This can be proved by several classical documents, Serat-serat Piwulang written by some authors in the renaisance era of  modern Javanese Letters like Serat Wulangreh, Serat Suluk Cipta Waskitha, Serat Suluk Haspiya, Serat Wedhatama, Serat Centhini, and Serat Wirit Hidayat Jati etc.. These documents are needed  investigating for  understanding the construction of  Javanese culture. The classical texts are not narration living in the vacuum history, space and time. On contrary, they are the variables and  values those must be explained in its era context. So, the understanding of  Javanese culture articulation in many Serat Piwulang of  Java gives some special uniqueness in understanding the Javanese culture.